2008
DOI: 10.5507/fot.2008.013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the coagulant PAX-18 on Planktothrix agardhii bloom in a shallow eutrophic fishpond.

Abstract: Abstract:For the first time in the Czech Republic, the PAX-18 coagulant has been used to restore a eutrophic fishpond. The polyaluminium hydrochloride coagulant was applied repeatedly to a shallow eutrophic fishpond in spring 2005. Two cylindrical plastic enclosures were used to isolate parts of the pond as untreated controls. Selected environmental variables were measured in situ. Water samples were analyzed regularly for nutrients, chlorophyll a concentration and phytoplankton abundance and structure with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Masuda and Boyd () showed that treatments with aluminum sulfate, or alum, reduces soluble reactive phosphorus and total phosphorus concentrations in catfish ponds. They did not evaluate the effects on cyanobacterial abundance or off‐flavor incidence but studies in other water bodies (De Julio, Fioravante, De Julio, Oroski, & Graham, ; Lam & Prepas, ), including fishponds in the Czech Republic (Lelkova et al, ), show that addition of aluminum salts can remove cyanobacterial cells from water, implying that production of odorous compounds may be interrupted, at least temporarily. And that is the catch—addition of aluminum salts to water does not cause a long‐term increase in Al 3+ concentrations because aluminum ions are quickly converted to insoluble aluminum hydroxides that precipitate to the bottom.…”
Section: Preventing Cyanobacterial Off‐flavorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masuda and Boyd () showed that treatments with aluminum sulfate, or alum, reduces soluble reactive phosphorus and total phosphorus concentrations in catfish ponds. They did not evaluate the effects on cyanobacterial abundance or off‐flavor incidence but studies in other water bodies (De Julio, Fioravante, De Julio, Oroski, & Graham, ; Lam & Prepas, ), including fishponds in the Czech Republic (Lelkova et al, ), show that addition of aluminum salts can remove cyanobacterial cells from water, implying that production of odorous compounds may be interrupted, at least temporarily. And that is the catch—addition of aluminum salts to water does not cause a long‐term increase in Al 3+ concentrations because aluminum ions are quickly converted to insoluble aluminum hydroxides that precipitate to the bottom.…”
Section: Preventing Cyanobacterial Off‐flavorsmentioning
confidence: 99%
“…And that is the catch—addition of aluminum salts to water does not cause a long‐term increase in Al 3+ concentrations because aluminum ions are quickly converted to insoluble aluminum hydroxides that precipitate to the bottom. Because there is little residual effect, conditions soon return to those existing before treatment unless direct inputs of phosphorus are concurrently and permanently reduced (Lelkova et al, ). The lack of long‐lasting effects of aluminum salts will be especially noticeable in catfish ponds where phosphorus concentrations increase quickly in response to large, daily inputs of phosphorus from feed.…”
Section: Preventing Cyanobacterial Off‐flavorsmentioning
confidence: 99%
“…In jar tests, Pan et al found (2006a) a removal efficiency of up to 95 % in 75 min for Microcystis aeruginosa, depending on the salinity and chitosan modification of the used sepiolite and kaolinite. In a 32 m 2 enclosure in Lake Taihu, a removal efficiency of 99 % of chlorophyll a (i.e., from 2000 to 20 lg l -1 ) and 42 % of dissolved phosphate was obtained with chitosan-modified local soils (Pan et al 2006b (Lelkova et al 2008;De Julio et al 2010;Jančula and Maršálek 2011). Lelkova et al (2008) successfully flocculated Planktothrix agardhii dosing PACl in a fishpond.…”
Section: Chemicalmentioning
confidence: 99%
“…In a 32 m 2 enclosure in Lake Taihu, a removal efficiency of 99 % of chlorophyll a (i.e., from 2000 to 20 lg l -1 ) and 42 % of dissolved phosphate was obtained with chitosan-modified local soils (Pan et al 2006b (Lelkova et al 2008;De Julio et al 2010;Jančula and Maršálek 2011). Lelkova et al (2008) successfully flocculated Planktothrix agardhii dosing PACl in a fishpond. Sulfate compounds are less suitable due to the possible formation of iron sulfide (FeS), which reduces the phosphate binding capacities of lake sediments (Hansen et al 2003).…”
Section: Chemicalmentioning
confidence: 99%
“…Free dissolved phospho-rus and nitrogen are important nutrients for photosynthetic organisms [5], mainly for cyanobacterial blooms [6,7]. Eutrophication causes considerable changes in biochemical cycles and biological communities [8]. Community interaction in pelagic food webs is affected by large scale of physical, chemical and biological processes and are govern by nutrient limitation, competition, predation and other ecological forces [9,10].…”
Section: Introductionmentioning
confidence: 99%